Simplify each expression

1. 25⁰

2. ( m⁴n⁴)

3. (8⁰)⁰

4. 4a²b⁰

5. -(ab)⁰​


Sagot :

Answer:

1. 1

2. (mn)⁴

3. 1

4. 4a²

5. -1

EXPONENTS

==============================

[tex] \large \begin{align}& \sf1. \: \: {25}^{0} \\& \sf \normalsize \implies \large \orange{1} \end{align}[/tex]

[tex] \: [/tex]

[tex] \large \begin{align}& \sf2. \: \: ( {m}^{4} {n}^{4} ) \\& \sf \normalsize \implies \large \orange{ {(mn)}^{4} } \end{align} \\[/tex]

[tex] \: [/tex]

[tex] \large \begin{align}& \sf3. \: \: {( {8}^{0} )}^{0} \\& \sf \normalsize \implies \large { (1 )}^{0} \\& \sf \normalsize \implies \large \orange{1} \end{align}[/tex]

[tex] \: [/tex]

[tex] \large \begin{align}& \sf4. \: \: 4 {a}^{2} {b}^{0} \\& \sf \normalsize \implies \large {4 {a}^{2} \cdot1 }\\& \sf \normalsize \implies \large \orange{4 {a}^{2} } \end{align}[/tex]

[tex] \: [/tex]

[tex]\large \begin{align}& \sf5. \: \: - {(ab)}^{0} \\& \sf \normalsize \implies \large - ( {a}^{0} {b}^{0}) \\& \sf \normalsize \implies \large - ( 1 \cdot1) \\& \sf \normalsize \implies \large - ( 1)\\& \sf \normalsize \implies \large \orange{ - 1 } \end{align}[/tex]

[tex] \: [/tex]

Note:

When the base has a zero exponent, the value will always be 1.

==============================

#CarryOnLearning

(ノ^_^)ノ